Mechanism of NbC as heterogeneous nucleus of M3C in CADI: first principle calculation and experiment research - Penghui Yang; Hanguang Fu; Xingye Guo; Bennacer Rachid; Jian Lin (Journal of Materials Research and Technology, 2020)
The phase precipitation curves of carbidic ductile iron with Nb element were simulated by the thermodynamic module in JMatPro software. The lattice mismatch between NbC and M3C was analyzed using Bramfitt two-dimensional mismatch theory, and the bonding strength (adhesive work) and interface stability (interfacial energy) of M3C(100)/NbC(110) interface were calculated by using the first principles method. The microstructure of carbidic austempered ductile iron (CADI) was observed by scanning electron microscope (SEM) and transmission electron microscope (TEM). The results show that NbC particles precipitate previously at 1420 °C, and the lattice mismatch of M3C(100)/NbC(110) is 3.75 %. Six interface models have been constructed according to different case and termination conditions, in which interface adhesive work of Case I/C interface is the largest (1.35 J/m2), interfacial energy of Case I/Fe interface is the smallest. The covalent bond has been formed on the interface, which proves that M3C(100) and NbC(110) can form a stable interface. The experimental results confirm the precipitation of NbC particles. In addition, M3C grows beside NbC particles and they are combined tightly, indicating that NbC can act as an effective heterogeneous nucleation site of M3C.